PERANCANGAN PEMBANGKIT GELOMBANG ULTRASONIC VARIABEL MENGGUNAKAN MIKROKONTROLER ATMEGA 16 - Herdianto; Adisastra Pengalaman Tarigan (Universitas Harapan Medan, 2020)
One of the factors causing the decline in national rice production is the attack of pests on rice. Based on data obtained from the agricultural department which has been processed by local data, it is known that there are 6 types of pests that attack rice plants in Indonesia, namely brown planthoppers, rats, rice stem borer, blast, kresek leaves and tungro. One method that can be used to repel pests in rice is by utilizing ultrasonic waves but is still limited to a range of only 4 meters in intensity. Therefore, a research aimed at generating ultrasonic waves will be carried out with the intensity of the ultrasonic wave range reaching 20 meters. The stages of research carried out include collecting data, analyzing data, designing circuit design, implementing circuit design, testing circuit design implementation and testing circuit design implementation. The ultrasonic wave generator designed in this study consists of 2 parts, namely a frequency generator of 20 - 50Khz and an amplifier of the output amplitude. Tests carried out in the research are still on the frequency generator section and the results show that the frequency variation of 20 - 50Khz can be produced properly by the ATMEGA 16 microcontroller.